'A quintessentially English designer' from Durban: Victor Stiebel's South African Childhood (1968). Issue 3 (1st July 2022) - Stiebel, Lindy
Victor Stiebel (1907‐76), in his obituary in The Times, was described as a well known and highly esteemed British couturier. Yet, for the first eighteen years of his life, Stiebel lived unremarkably in Durban, South Africa, with his middle-class colonial family. In an article written by a fashion historian who appraised his importance within the British fashion industry, Stiebel is described as the quintessential English designer. How did this 'Englishness' develop and what evidence do we see of this quality in his autobiography South African Childhood (1968) that covers his childhood years? The leap from Durban to London and his subsequent career as a court dressmaker and couturier, plus designer for Hollywood stars including Vivien Leigh and Katherine Hepburn, is vast, but it is one that Stiebel eagerly made. The bridge, this article argues, is the very 'Englishness' that Stiebel encountered in his home and the colonial society of Durban in the Edwardian era in which he grew up. Life in the colonies concentrated this quality in its settlers probably because of their distance from the metropole rather than their proximity. This article sets out to examine what form this 'Englishness' took in Stiebel's life and work, evident visually in his dress designs according to fashion historians, but also, from a literary historian's point of view, in his autobiographical writing and written correspondence, particularly that with the actress Vivien Leigh.